Pengaruh Latihan Rhythmic Stabilization Terhadap Peningkatan Aktivitas Fungsional Pada Pekerja Laundry Yang Mengalami Nyeri Punggung Bawahmyogenic Di Desa Pabelan - Sari, Rinda Aulia Novita, Umi Budi Rahayu, S. Fis., M. Kes (2016)
Background: Laundry is one of informal business type,which has been growing rapidly in the comunity. Laundry workers are generally conducted in drying, squeezing, rinsing, lifting, folding, ironing. These are causing to musculoskeletal disorder as generlly complained in the low back pain and decreased functional activity can do some exercises of rhythmic stabilization. Objective: To investigate the effect of exercise rhythmic stabilization to invrease the functional activity of the laundry workers who have experienced in the low back pain myogenic. Methods: Research using Quasi Experimental research design Pre and Post Two Group design by comparing two groups namely, drills rhythmic stabilization and not given rhythmic stabilization exercises conducted over 4 weeks with 12 respondents. Techniques of analysis data in this study using the wilcoxon to test the influence. Result: The result of the study are the effect of given exercises in rhythmic stabilization and not given rhythmic stabilization exercise by using the wilcoxon test. The wilcoxon test are exercises rhythmic stabilization with the result p= 0.027, its means that p < 0.05 can be concluded that there is significant influence against increasing functional activity and not given rhythmic stabilization exercise with the results p= 0.180, it means that p > 0.05 can be concluded that there is no significant effect with the increasing of functional activity. Conclusions: there was a significant influence to increase the functional activity against on low back pain myogenic. Keywords: rhythmic stabilization, low back pain, functional activity.